Agile CD22 nanoclusters run rings around fenced BCR. (8th January 2016) - Depoil, David; Dustin, Michael L
Abstract : B lymphocytes are key players in host defence, but also autoimmune diseases. Their survival depends upon tonic signals transduced by surface immunoglobulin (BCR) and the process leading to antibody secretion is initiated by interaction of BCR with a cognate antigen. CD22 limits signalling of the BCR to strike a balance between tonic signalling, reactivity to pathogens and prevention of autoimmunity. In this issue, Gasparrini et al (2016) combined super‐resolution imaging approaches with single‐particle tracking and simulations to show how CD22 controls the signalling state of the BCR. They demonstrated that small CD22 nanoclusters run rings around the BCR in confined steady state to maintain low tonic signals, but releasing BCR from these corrals allows BCR cluster growth, which overcomes the harrying inhibition from highly mobile CD22. Abstract : Super‐resolution imaging approaches reveal how fast diffusion allows few molecules of CD22 to sample and inhibit a large number of immobile B‐cell receptor nanoclusters.